Rehabilitasi terhadap Korban Penyalahgunaan Narkotika di Badan Narkotika Nasional Provinsi Bali - I Made Subantara; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2020)
Narcotics continues to be produced at this time in addition to medicine as well as for the development of scientific studies. Narcotics, on the one hand, is a drug or substance that is useful in the field of medicine or health services and scientific development, on the other hand, it can lead to dependence and cause harm if it is not used properly and without strict and careful control and supervision. When used irregularly according to dosages, it can be physically and mentally damaging for those who use it to become dependent. This study aims to determine the procedures for implementing rehabilitation of victims of narcotics abuse and the obstacles faced by the National Narcotics Agency of Bali Province in rehabilitating narcotics abuse at the National Narcotics Agency of Bali Province. This research uses the normative method because there are still vague norms, based on the opinion of the undergraduate law and law.